OPTIMIZATION OF DENATURATION TEMPERATURE AND TIME USING REAL-TIME PCR METHOD IN HEPATITIS B TEST - Tanti Yulia Dewi; Fusvita Merdekawati; Ai Djuminar; Yogi Khoirul Abror (Journal of Vocational Health Studies, 2024)
Background: The hepatitis B test can be conducted using the real-time PCR method. In chronic cases, the test is performed by detecting one of the Hepatitis B Virus (HBV) specific genes, HBcAg. The real-time PCR method requires optimization to obtain optimal results. Purpose: This research aims to determine the optimal temperature and time for denaturation in the hepatitis B test using the real-time PCR method. Method: The research method used was a quasi-experiment involving variations in temperature (94 °C, 95 °C, and 96 °C) and time (10 seconds, 15 seconds, and 20 seconds) for denaturation. Data processing resulted in static group comparisons based on 27 primary data from the Cycle Threshold (CT) value. Result: Variations in temperature conditions, specifically at 94 °C, 95 °C, and 96 °C, combined with a denaturation time of 10 seconds, yielded the mean CT values of 26.495, 26.355, and 26.003, respectively. When the temperature conditions were maintained at 94 °C, 95 °C, and 96 °C, with a denaturation time of 15 seconds, yielded the mean CT values of 25.962, 25.641, and 25.396. Similarly, under temperature conditions of 94 °C, 95 °C, and 96 °C with a denaturation time of 20 seconds, yielded the mean CT values of 26.544, 26.505, and 25.830 were obtained. Conclusion: Optimal results in this study are obtained through the acquisition of the smallest CT value, namely at temperature conditions of 96 °C and 15 seconds.